Optimal combination strategy of left atrial appendage closure plus catheter ablation in a single procedure in patients with nonvalvular atrial fibrillation. (6th June 2018) - Du, Xianfeng; Chu, Huimin; He, Bin; Wang, Binhao; Liu, Jing; Feng, Mingjun; Yu, Yibo; Fu, Guohua; Jin, He; Gao, Fang; Zhu, Jingjing; Chen, Xiaomin
Abstract: Background: The efficacy and safety of combining left atrial appendage closure (LAAC) plus atrial fibrillation (AF) catheter ablation (CA) in a single procedure has been established, but the optimal combination strategy has not been thoroughly elucidated to date. Objective: We aimed to investigate the impact of different combination strategies on clinical outcomes. Methods: Eighty‐two consecutive patients with symptomatic AF (mean CHA2 DS2 ‐VASc score 4.4 ± 1.4, mean HAS‐BLED score 3.5 ± 1.0) were enrolled. LAAC with the Watchman device was performed either before (occlusion‐first group, N  =  52) or after (ablation‐first group, N  =  30) CA. Procedural and clinical data were retrospectively analyzed to evaluate the advantages of each strategy. Results: Complete device occlusions were achieved in 92.3% and 90.0% of patients, respectively (P    =  0.719). Neither acute nor chronic peridevice leak greater than 5 mm was detected. Oral anticoagulants were held in all patients, except two (one in each group) with asymptomatic device‐related thrombi. AF‐free success rates were comparable between groups with a mean follow‐up of 11.2 ± 7.3 months (75.0% vs. 70.0%, log‐rank P    =  0.311). The new peridevice leak rate was significantly lower in the occlusion‐first group (7.7% vs. 26.7%, P    =  0.019). Multivariate logistic regression demonstrated that the combination strategy was independently associated with the new peridevice leak (P    =  0.025, OR 13.3). Conclusions: Both occlusion‐first and ablation‐first strategies were efficacious and safe as combined procedures in patients with nonvalvular AF; however, the occlusion‐first strategy was associated with lower new peridevice leak rates at follow‐up.